T2-signal intensity, SSTR expression, and somatostatin analogs efficacy predict response to pasireotide in acromegaly. Issue 6 (June 2020) - Coopmans, Eva C; Schneiders, Joppe J; El-Sayed, Nour; Erler, Nicole S; Hofland, Leo J; van der Lely, Aart-Jan; Petrossians, Patrick; Potorac, Julia; Muhammad, Ammar; Neggers, Sebastian J C M M
Abstract : Objective: T2-signal intensity and somatostatin (SST) receptor expression are recognized predictors of therapy response in acromegaly. We investigated the relationship between these predictors and the hormonal and tumoral responses to long-acting pasireotide (PAS-LAR) therapy, which were also compared with responsiveness to first-generation somatostatin receptor ligands (SRLs). Design: The PAPE study is a cohort study. Methods: We included 45 acromegaly patients initially receiving SRLs, followed by combination therapy with pegvisomant, and finally PAS-LAR. We assessed tumor volume reduction (≥25% from baseline), IGF-1 levels (expressed as the upper limit of normal), and T2-weighted MRI signal and SST receptor expression of the adenoma. Results: Patients with significant tumor shrinkage during PAS-LAR showed higher IGF-1 levels during PAS-LAR (mean (S.D.): 1.36 (0.53) vs 0.93 (0.43), P = 0.020), less IGF-1 reduction after first-generation SRLs (mean (S.D.): 0.55 (0.71) vs 1.25 (1.07), P = 0.028), and lower SST2 receptor expression (median (IQR): 2.0 (1.0–6.0) vs 12.0 (7.5–12.0), P = 0.040). Overall, T2-signal intensity ratio was increased compared with baseline (mean (S.D.): 1.39 (0.56) vs 1.25 (0.52), P = 0.017) and a higher T2-signal was associated with lower IGF-1 levels during PAS-LAR (β: −0.29, 95% CI: −0.56 to −0.01, P = 0.045). A subset of PAS-LAR treated patients with increased T2-signal intensity achieved greater reduction of IGF-1 (mean (S.D.): 0.80 (0.60) vs 0.45 (0.39), P = 0.016). Conclusions: Patients unresponsive to SRLs with a lower SST2 receptor expression are more prone to achieve tumor shrinkage during PAS-LAR. Surprisingly, tumor shrinkage is not accompanied by a biochemical response, which is accompanied with a higher T2-signal intensity.